2014
DOI: 10.3109/02770903.2014.957765
|View full text |Cite
|
Sign up to set email alerts
|

Increased sympathetic modulation and decreased response of the heart rate variability in controlled asthma

Abstract: Controlled asthma in adults appears to induce an increased sympathetic modulation and attenuated response to the postural changes and the M-RSA. Furthermore, there is a correlation between the airways' obstruction and HRV, especially during postural changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
2
21
0
5
Order By: Relevance
“…Previous results regarding heart rate variability in asthmatic subjects have already been published by our group. 15 However, ß 2 -agonist bronchodilators could be administered at any time, under a previous medical prescription (investigator and pulmonologist linked to the study), to revert the bronchoconstriction response after exercise if the volunteer presented significant dyspnea or if FEV 1 had not returned to within 10% of baseline when the subject was ready to leave the laboratory. 16 On the second day of the protocol, the second ISWT was conducted and, after a minimum of 48 h and a maximum of 1 week, subjects performed the third ISWT.…”
Section: Methodsmentioning
confidence: 99%
“…Previous results regarding heart rate variability in asthmatic subjects have already been published by our group. 15 However, ß 2 -agonist bronchodilators could be administered at any time, under a previous medical prescription (investigator and pulmonologist linked to the study), to revert the bronchoconstriction response after exercise if the volunteer presented significant dyspnea or if FEV 1 had not returned to within 10% of baseline when the subject was ready to leave the laboratory. 16 On the second day of the protocol, the second ISWT was conducted and, after a minimum of 48 h and a maximum of 1 week, subjects performed the third ISWT.…”
Section: Methodsmentioning
confidence: 99%
“…A recent Cochrane review demonstrated that individual trials reported positive effects of breathing exercises, but authors concluded that no reliable conclusions could be drawn concerning the use of breathing exercises in asthma control [10]. In our opinion, breathing exercise will reduce anxiety and depression levels, which seem to be associated with dysfunctional breathing such as hyperventilation [16] normalizing, thus, the autonomic system [45]. …”
Section: Discussionmentioning
confidence: 99%
“…-ECG recorded connection; -Two static volume measurements using a dilution technique (normal breathing frequency: respiratory rate of 20-25/min): 5 min for each recording. These two measurements allowed the calculation of the static volumes as recommended (Wanger et al, 2005); -One functional residual capacity (FRC) measurement using a dilution technique with slow-paced breathing recording at six cycles per minute [5 s of inspiration, 5 s of expiration: 5 min as previously described (Garcia-Araújo et al, 2015)] in order to study respiratory sinus arrhythmia (RSA) that is recognized as a physiological mechanism to ensure optimal ventilation-perfusion matching within the lungs (Hayano and Yuda, 2019); -Exhaled NO measurement at multiple flow rates to calculate alveolar NO concentration (C alv,NO ) and maximal bronchial NO flux (J' aw,NO ) as previously described (Mahut et al, 2004). J' aw,NO has been correlated to both subepithelial eosinophilic infiltration and reticular basement membrane thickness, two asthma characteristics (Mahut et al, 2004).…”
Section: Pulmonary Function Tests and Hrv Analysismentioning
confidence: 99%
“…Sample size calculation. We planned to include 30 children in each group of patients based on the number of patients included in the previous studies devoted to the ANS function, involving asthmatic or SCD patients (Eryonucu et al, 2001;Pearson et al, 2005;Knight-Madden et al, 2013;Garcia-Araújo et al, 2015).…”
Section: Statistical Analysesmentioning
confidence: 99%